1994
DOI: 10.1063/1.466321
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of size-intensive transition moments from the coupled cluster singles and doubles linear response function

Abstract: Coupled cluster singles and doubles linear response (CCLR) calculations have been carried out for excitation energies and dipole transition strengths for the lowest excitations in LiH, CH+, and C4 and the results compared with the results from a CI-like approach to equation of motion coupled cluster (EOMCC) . The transition strengths are similar in the two approaches for single molecule calculations on small systems. However, the CCLR approach gives size-intensive dipole transition strengths, while the EOMCC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
201
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(203 citation statements)
references
References 14 publications
1
201
0
1
Order By: Relevance
“…The mathematical difference between LR and EOM formalisms arises when they are used to compute excitation properties, such as transition dipole and oscillator strengths. Jørgensen and coworkers have shown that the transition moment in LR-CC is size-intensive whereas EOM formalism is not, 13 although the difference in intensity between LR and EOM is very small for most computationally tractable systems. 27 In this work, we focus only on analyzing the performance of low-scaling alternatives to EOM-CCSD and LR-CCSD on excitation energies where these two formalisms are equivalent.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The mathematical difference between LR and EOM formalisms arises when they are used to compute excitation properties, such as transition dipole and oscillator strengths. Jørgensen and coworkers have shown that the transition moment in LR-CC is size-intensive whereas EOM formalism is not, 13 although the difference in intensity between LR and EOM is very small for most computationally tractable systems. 27 In this work, we focus only on analyzing the performance of low-scaling alternatives to EOM-CCSD and LR-CCSD on excitation energies where these two formalisms are equivalent.…”
Section: Theorymentioning
confidence: 99%
“…15 Despite their formal differences, LR-CC and EOM-CC when truncated at the same level of cluster operator will give the same value for excitation energies, although they differ with respect to transition properties. 13 In particular, the EOM-CC formalism 16,17 has led to extremely accurate and robust descriptions of excited states, yet may be prohibitively costly. The equation of motion coupled cluster singles and doubles (EOM-CCSD) 14,18 gives accurate qualitative and quantitative energies for most molecular systems, yet scales as O(N 6 ), making its application to large molecules difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical calculation of molecular properties must be implemented using integral-direct techniques, as the CCSD approach has proven to be successful in calculating several molecular properties in the framework of the response function formalism. 11 Particularly excitation energies 12 and transition matrix elements 13 have been computed, as well as frequency-dependent polarizabilities 14 and magnetic shielding tensors. 15 We have already implemented the calculation of the coupled cluster linear response ͑CCLR͒ excitation energies 16 directly from the AO integral distributions.…”
Section: Introductionmentioning
confidence: 99%
“…There exists two coupled cluster approaches for the computation of the transition moments between the ground and excited states, the linear response coupled cluster theory (LRCC) of Koch et al 16,17,19,20 and the coupled cluster expectation value formulation of the linear response function (XCC) of Tucholska et al 21 As already stated above, for the transition moments between the excited states, the only available approach is based on the quadratic response coupled cluster (QRCC) theory of Koch et al 16,17,19,20 In the present work we generalize the approach of Refs. 22 and 21 to the calculation of transition properties between the excited states.…”
Section: Introductionmentioning
confidence: 99%